The impact of a new coronavirus infection spread on the environment and on the public policy for environmental development - O. A. Filchenkova (Вестник университета)
The aim of the study is to carry out a SWOT analysis of the impact of the spread of a new coronavirus infection on the environment and on public policy for environmental development. The main strategic planning documents defining long-term priorities, goals and objectives of public administration in the field of environmental protection and ecological safety have been reviewed, the relevant domestic and foreign publications in this field have been studied, the materials of the websites of government authorities that publish information on the current situation and measures to support business and economy in connection with the COVID-19 pandemic as well as statistical and other data on the the environmental situation in Russia in recent years have been analysed. The impact of COVID-19 pandemic on the current state of the environment and the environmental effects of this impact have been shown, the main challenges and threats to environmental security have been described, opportunities have been formulated in the current situation and can be used in the development of state environmental policy. The problematic issues of waste management in the pandemic have been touched upon. Particular attention has been paid to measures to combat new coronavirus infection and to support the economy with regard to environmental management and protection issues, as well as to business support measures in relation to COVID-19 pandemic in the constituent entities of the Russian Federation. The conclusions drawn from the study indicate that there is scope for a stronger trend towards a green economy.